PARKING OCCUPANCY DETECTOR IN SMART PARKING SYSTEM - ORDA OLEKSIІ; BONDARENKO, NATALIIA; BONDARENKO, VIKTOR (Herald of Khmelnytskyi National University. Technical sciences, 2025)
This article presents the design and testing of a parking occupancy detection device, a key element of smart parking infrastructure. As cities face increasing vehicle density and parking shortages, there is a growing demand for affordable, autonomous, and scalable systems capable of accurately identifying vacant parking spots. The developed solution is based on the STM32F103C8T6 microcontroller, RCWL-1601 ultrasonic sensor, and ESP-07 Wi-Fi module. The proposed device features modular architecture and is designed for easy deployment and integration into existing urban infrastructure without requiring pavement modification. The system architecture consists of three main subsystems: input, processing, and output. The ultrasonic sensor detects vehicles based on distance measurements, while the microcontroller handles signal processing, occupancy status determination, memory buffering, and communication management. The ESP-07 module provides wireless data transmission to a server or mobile application. LED indicators offer realtime visualization of parking status, enhancing user convenience. Functional testing conducted on a model parking stand demonstrated high detection accuracy (±2 cm), low latency in wireless communication (up to 0.5 seconds), and energy-efficient performance suitable for battery-powered operation. The solution is ideal for covered parking areas and can be adapted for outdoor use following environmental testing. In addition to its base functionality, the device allows for future upgrades, including integration with cloud-based monitoring systems, implementation of additional communication interfaces (e.g., GSM, LoRaWAN), and support for intelligent algorithms like pattern recognition or parking time estimation. Security enhancements such as TLS encryption can also be embedded. Overall, the prototype provides a versatile and cost-effective platform for smart city applications, offering both localized operation and networked scalability. Comparative analysis with existing commercial solutions confirmed a significant cost reduction — up to 5–10 times while maintaining proper functionality.